EVIDENCE BASED CASE REPORT (EBCR): PENGARUH HIPNOBIRTHING TERHADAP PENURUNAN NYERI PERSALINAN KALA 1 FASE AKTIF - Fadhilah, Chagya; Pascawati, Riana; Ulfah Fatimah, Yulia (Jurnal Kesehatan Siliwangi, 2024)
Background: Labor pain is a physiological process that occurs during labour, where individual responses to pain vary. So it requires efforts to overcome labor pain using pharmacological and non-pharmacological methods, one of which is the hypnobirthing method. Purpose: This application aims to provide a positive experience for mothers during labour with a sense of comfort and calm during the labour process. Method: The literature e-database PubMed, Cochrane, Science Direct and Google Scholar was used to search for evidence. Results: In this case, the results showed changes in labour pain using VAS measurements. Discussion: Hypnobirthing works by activating nerves in the brain, causing the release of natural morphine-like substances called enkephalins and endorphins. So that it can increase the mother's tolerance to pain. Conclusion: Hypnobirthing method affect reducing labour pain.